Robot Arm Control System for Assisted Feeding of People With Disabilities in Their Upper Limbs - Daniella Arnáez; Fiorela Manco; José Oliden; Guillermo Kemper (Journal of Systemics, Cybernetics and Informatics)

(untitled)
This work proposes a robot arm control system for assisted feeding of people with reduced functionality in their upper limbs. It aims at improving their quality of life by helping users recover their independence when feeding, aided by the proposed system. Previous research presents solutions that often lack functionality to meet the user's needs, such as a lack of emergency functions or the use of passive feeding techniques, due to the absence of adequate human-robot interaction. The proposed solution involves the design of an interface adapter between the robot arm and the spoon, for the correct transport and positioning of the food. Moreover, a PD-type electronic controller is implemented for the robot arm; it includes gravity compensation and trajectories defined from the detection of the user's position. Additionally, the system has two safety features: an emergency button and a proximity warning that triggers when undesired objects are too close to the robot arm. The proposed system was validated through position tests and interaction with people using rice and oatmeal. When carrying out the tests with rice, 80% success was obtained, while in the case of oatmeal, 98.9% success was achieved.